Protective effect of fucoidan from Fucus vesiculosus on liver fibrosis via the TGF-β1/Smad pathway-mediated inhibition of extracellular matrix and autophagy - Li J; Chen K; Li S; Feng J; Liu T; Wang F; Zhang R; Xu S; Zhou Y; Zhou S; Xia Y; Lu J; et al. (Dove Medical Press, 2016)
Jingjing Li,1 Kan Chen,1 Sainan Li,1 Jiao Feng,1 Tong Liu,1 Fan Wang,1 Rong Zhang,1,2 Shizan Xu,1,2 Yuqing Zhou,1,3 Shunfeng Zhou,1,3 Yujing Xia,1 Jie Lu,1 Yingqun Zhou,1 Chuanyong Guo1 1Department of Gastroenterology, Shanghai Tenth People’s Hospital, Tongji University School of Medicine, Shanghai, 2The First Clinical Medical College of Nanjing Medical University, Nanjing, 3Department of Gastroenterology, The First Affiliated Hospital of Soochow University, Suzhou, People’s Republic of China Abstract: Liver fibrosis is a dynamic reversible pathological process in the development of chronic liver disease to cirrhosis. However, the current treatments are not administered for a long term due to their various side effects. Autophagy is initiated to decompose damaged or excess organelles, which had been found to alter the progression of liver fibrosis. In this article, we hypothesized that fucoidan from Fucus vesiculosus may attenuate liver fibrosis in mice by inhibition of the extracellular matrix and autophagy in carbon tetrachloride- and bile duct ligation-induced animal models of liver fibrosis. The results were determined using enzyme-linked immunosorbent assay, quantitative real-time polymerase chain reaction, Western blotting, and immunohistochemical staining. Fucoidan from F. vesiculosus could inhibit the activation of hepatic stellate cells and the formation of extracellular matrix and autophagosomes, and its effect may be associated with the downregulation of transforming growth factor beta 1/Smads pathways. Fucoidan, as an autophagy and transforming growth factor beta 1 inhibitor, could be a promising potential therapeutic agent for liver fibrosis. Keywords: liver cirrhosis, hepatic stellate cells, bile duct ligation